Propuesta para la mejora de propiedades antideslizantes de la suela del calzado de seguridad para la empresa Croydon Colombia S.A. (2020)
This project aims to implement a proposal for improving the anti-slip properties of the sole of safety footwear for the company Croydon Colombia S.A., in the development was carried out a diagnosis of the current characteristics of these boots, using the compounds that are injected into the different production lines and the standard footprint, for this was standardized in testing the resistance to slipping following the guidelines of the standards NTC ISO 20344: 2012, NTC ISO 20345:2011 and NRF 056 PEMEX:2006. The design of experiments was performed considering the coefficient of friction as a response variable and the variables needed to perform the tests were determined, which are described in the third chapter of this document. For the first test, four compounds (Z-153, Z-155, Z-193 and Z-178) and the base geometry were used to carry out the diagnosis of the anti-slip property of the named compounds.